1999
DOI: 10.2307/2641398
|View full text |Cite
|
Sign up to set email alerts
|

Frost Followed the Plow: Impacts of Deforestation on the Climate of the United States

Abstract: The modern vegetated landscape of the United States little resembles the ''natural'' landscape prior to colonial settlement. Two 10-yr climate simulations with a global climate model using natural and modern vegetation maps for land surface boundary conditions showed that the conversion of forest to cropland in the eastern and central United States cooled climate. Mean annual surface air temperature decreased by 0.6Њ-1.0ЊC in the United States east of 100Њ W. The decrease in daily maximum temperature exceeded … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2001
2001
2021
2021

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 31 publications
3
29
0
Order By: Relevance
“…Our approach compared a natural vegetation scenario to a bareground scenario and thus estimated the potential contribution of natural ecosystems to biophysical climate regulation, but conversion of natural land to other land-cover types can have different results. For example, replacing forest with bare ground in this study generally increased air temperature, however, in the US, conversion of forests to croplands generally decreases air temperature (Bonan 1999(Bonan , 2001. Both bare ground and croplands absorb less incoming sunlight, but croplands and forests transpire similar amounts of water.…”
Section: N Limitations Of the Climate Regulation Indexmentioning
confidence: 61%
“…Our approach compared a natural vegetation scenario to a bareground scenario and thus estimated the potential contribution of natural ecosystems to biophysical climate regulation, but conversion of natural land to other land-cover types can have different results. For example, replacing forest with bare ground in this study generally increased air temperature, however, in the US, conversion of forests to croplands generally decreases air temperature (Bonan 1999(Bonan , 2001. Both bare ground and croplands absorb less incoming sunlight, but croplands and forests transpire similar amounts of water.…”
Section: N Limitations Of the Climate Regulation Indexmentioning
confidence: 61%
“…BONAN ET AL. : PLANT FUNCTIONAL TYPES AND CLIMATE MODELS on climate [Bonan, 1995b], the effect of vegetation and soil [Kutzbach et al, 1996] and lakes and wetlands [Coe and Bonan, 1997] on the African monsoon in the middle Holocene, the effect of soil water on floods and droughts in the Mississippi River basin [Bonan and Stillwell-Soller, 1998], the effect of tundra ecosystems on arctic climate [Lynch et al, 1999], and the effects of temperate deforestation on climate [Bonan, 1997[Bonan, , 1999.…”
Section: -6mentioning
confidence: 99%
“…www.frontiersinecology.org © The Ecological Society of America deforestation in the Amazon may therefore be a significantly warmer and somewhat drier local climate. While the impacts of tropical deforestation have received considerable attention, other studies have shown that land-use and land-cover change in semi-arid (Zeng et al 1999;Wang and Eltahir 2000a, 2000b, 2000c, 2000d, temperate (Copeland et al 1996;Bonan et al 1997Bonan et al , 1999Reale and Dirmeyer 2000;Reale and Shukla 2000;Heck et al 2001) and boreal ecosystems (Bonan et al 1992(Bonan et al , 1995 can also greatly affect the climate.…”
Section: Biophysical Impacts Of Changing Land Use and Covermentioning
confidence: 99%